PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA MEMPERLUAS STRATEGI PEMASARAN PADA UMKM ABON KEPALA SAPI - Alfu Laila; Dakusta Puspitasari (khidmatan, 2021)
MSME Shredded Cow Head is one of the MSMEs located in Tosari Hamlet, Kebonagung, Tegalrejo. This MSME has been established since the 1970s and is now in the 2nd generation. In this study, there are several obstacles, namely the MSME Shredded Head Cows do not understand much about technological knowledge and do not have a strategy to develop an online business. Besides that, the MSMEs also have difficulty in carrying out these business bookkeeping reports. The method used in this study is the ABCD method by collecting data in the form of interviews. This study aims to provide changes to marketing strategies through social media and marketplaces so that MSME actors can expand their marketing reach.